Azaleas : a Book of Poems. - Sowol, Kim (Weatherhead Books on Asia, 2007)
Available for the first time in English, Azaleas is a captivating collection of poems by a master of the early Korean modernist style. Published in 1925, Azaleas is the only collection Kim Sowol (1902-1934) produced during his brief life, yet he remains one of Korea's most beloved and well-known poets. His work is a delightful and sophisticated blend of the images, tonalities, and rhythms of traditional Korean folk songs with surprisingly modern forms and themes. Sowol is also known for his unique and sometimes unsettling perspective, expressed through loneliness, longi.